Prevalence of Autism Spectrum Disorder in the Centro region of Portugal: a population based study of school age children within the ASDEU project - Rasga, Célia; Santos, João Xavier; Café, Cátia; Oliveira, Alexandra; Duque, Frederico; Posada, Manuel; Nunes, Ana; Oliveira, Guiomar; Vicente, Astrid Moura (Frontiers in Psychiatry, 2023)
Introduction Accurate prevalence estimates for Autism Spectrum Disorder (ASD) are fundamental to adequately program medical and educational resources for children. However, estimates vary globally and across Europe, and it is therefore wise to conduct epidemiological studies in defined geo-cultural contexts. Methods We used a population screening approach to estimate the prevalence of ASD in the Centro region of Portugal, using a harmonized protocol as part of the Autism Spectrum Disorders in the European Union (ASDEU) project. Results The overall prevalence was estimated at 0.5% (95% CI 0.3–0.7), higher in schools with Autism Units (3.3%, 95%CI 2.7–3.9) than in regular schools (0.3%, 95% CI 0.1–0.5) or schools with Multiple Disability Units (0.3%, 95% CI 0.04–0.6). Discussion The results indicate that the diagnosis of ASD is followed by the most effective educational policies in Centro Region. The variability in prevalence estimates across the different regions from the ASDEU project, and globally, is discussed.